Komunikasi Pemerintah dalam Penyebaran Informasi Publik melalui Website pada Diskominfo Kota Samarinda - Dariska Nur Laila Sifa; Letizia Dyastari (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2024)
The results of this research show that the implementation of government communication in managing and disseminating public information through websites by the Samarinda City Diskominfo based on Lasswell's Communication theory has been implemented well as an informative medium. There are several actors starting from the Head of Service, Secretary, Head of Division, and staff who provide public information such as agendas, government news, public documents, and others by paying attention to the characteristics of information quality, namely accurate, timely, relevant, and complete. The strategy implemented by Diskominfo Samarinda City in disseminating public information applies the four stages of e-government development, namely web presence, interaction, transactions and transformation. The existence of transformation with other public bodies helps the community to get a response from the feedback provided such as aspirations, complaints and requests for public information which aims to create better communication between the government and the community. However, feedback via the Samarinda City Diskominfo website helpdesk still needs to be maximized because there is no response from the admin who manages it. Apart from that, it is necessary to add a download menu to make it easier to search for public documents in the process of interaction by the public.